Poznavanje in uporaba prehranskih dodatkov med moškimi, ki se ukvarjajo s fitnesom, ter analiza njihove telesne sestave - Zaletel, Petra (Šport (Ljubljana), 2024)
Various groups of people, including athletes and recreational fitness enthusiasts, use dietary supplements (DS) to facilitate their performance during exercise. The accessibility of DS is increasing, but many users lack sufficient knowledge for their proper use. The main purpose of the research was to assess the knowledge and extent of DS use among men engaged in fitness. Additionally, we were interested in whether the body composition of those using DS differs from men who exercise in fitness but do not use DS. The study included 123 men, aged 18 to 50, regularly involved in fitness training for at least a year. Basic information, as well as data on DS knowledge and usage, was obtained through a questionnaire. Body composition was measured using a Tanita scale (model BC-545). Analysis of variance (ANOVA) was employed to determine differences in body composition between men using DS and those who do not, as well as to assess differences between two age groups of men (up to 40 and over 40 years). The results showed that 84% of men engaged in fitness use DS. Men using DS tend to be taller, have a lower percentage of body fat, and less muscle mass compared to those not using DS. A majority of men (54%) engaged in fitness training demonstrated poor knowledge about DS. On average, older individuals have a higher percentage of body fat and higher vital age compared to younger individuals.
Keywords: body composition; dodatki; exercise; fitnes; fitness; nutrition; prehrana; sport; supplements; šport; telesna sestava; training; trening; vadba